Air volume resonances and their influence on hall acoustics - V. STAUSKIS; V. KUNIGELIS (Archives of Acoustics, 2014)
The influence of resonances in a small rectangular music-hall on its reverberation characteristics was investigated. The length, width and height of the hall are 13.6 x 10.7 x 7 m, respectively. The sound absorption coefficients of all the hall surfaces are very small and equal to 0.03-0.05 through the whole frequency range. It has been established experimentally that the attenuation of the sound field in the empty hall is close to an exponential one. When 120 and 170 semi-upholstered chairs are placed in the hall, the sound field is characterized by early and steep attenuation which is determined by an additional sound absorption and by the late and slow attenuation determined by the repetitive echoes and resonances between the rows of chairs. The late character of attenuation starts from about 700-800 ms and depends on the distance between the microphone and the source. When the number of semi-upholstered chairs arranged in rows is increased from 120 to 170, the reverberation time up to 160 Hz, approximated by the attenuation from 0 to -30 dB, is not reduced, as one would expect, but grows from 5-6 s to 9-10 s and is even longer than the reverberation time of the empty hall. The late reverberation time of approximately -25 to -30 dB at 160 Hz has a pronounced resonant character and equals 12 s. On increasing the number of chairs to 170, the reverberation time peaks at 100 Hz achieves as much as 20 s. The late reverberation time shows that there exist resonances in the hall, evoked by a repetitive echo. After eliminating the echo, the resonances disappear.